Epidemiological Investigation of Canine Mammary Tumors in Mainland China Between 2017 and 2021 - Zheng, Hui-Hua; Du, Chong-Tao; Yu, Chao; Zhang, Yu-Zhu; Huang, Rong-Lei; Tang, Xin-Yue; Xie, Guang-Hong (Frontiers in Veterinary Science, 2022)
Epidemiological studies enable us to analyze disease behavior, define risk factors and establish fundamental prognostic criteria. This study aimed to determine the epidemiological and clinical characteristics of canine tumors diagnosed during the years 2017-2021. The results showed that canine mammary tumor was the most common tumors, and its relative incidence for five-years-total was 46.71% (504/1079), with 48.41% (244/504) of benign and 51.59% (260/504) of malignant. Pure breeds accounted for 84.13% (424/504) of submissions, and adult female dogs (9 to 12 years old) were most frequently involved, followed by 5- to 8-year-old females. Remarkably, 2.58% (13/504) occurred on the male dogs. In addition, a high prevalence of mammary tumors (77.38%, 390/504）was diagnosed in unneutered dogs, and different incidence rates were observed in different regions (Northeast, Southeast, Northwest and Southwest China). For clinical factors, the tumor size ranged from 0.5 to 28 cm, with the 0-5 cm of most common tumor size (47.82%, 241/504), and malignant tumors (4.33±2.88 cm, mean±SD) were bigger than benign ones (3.06±1.67 cm, mean±SD) (p<0.001). The incidence of single tumor (55.36%, 279/504) was higher than that of multiple tumors in dogs, while the latter had a higher incidence of malignant tumors (74.67%, 168/225). According to this study, we also found that canine mammary tumor was more common in the last two pairs of mammary glands. Additionally, multiple linear regression analysis showed that there was linear significant relationship between three independent variables (age, tumor size and tumor number) and histological properties of canine mammary tumor ((p>|t|)<0.05). This is the first retrospective statistical analysis of such a large data set in China to reveal the link between epidemiological-clinical risks and histological diagnosis. It aids to the improvement of the host's knowledge of canine tumor disorders and the early prevention of canine mammary tumors.